Distribution and Phytocomponent in the Ethanol Extract of Globba candida Gagnep. (Zingiberaceae) by GC-MS Analysis - Putri Sri Andila; I Gede Tirta (Journal of Tropical Life Science, 2019)
Globba is the third largest genera in the Zingiberaceae family, distributed in tropical and sub-tropical regions with the center of biodiversity in Southeast Asia. The study about phytochemical contents Globba is an interesting especially Globba candida Gapnep which have been never reported. The aims of this study were to observe distribution and phytochemical compounds of ethanol extract of G. candida Gapnep. found on Bali Island. Hydrodistillation was used to determine the presence of its essential oil and a Gas Chromatography-Mass Spectrometry (GC-MS) was used to carry out the phytochemical analysis of the essential oil and ethanol extracts of G. candida Gapne. The phytochemical analysis of the rhizomes and leaves ethanol extracts of G. candida Gapnep revealed 36 and 8 identified chemical compounds representing 85,82% and 85,47% of the total analyzed extracts. However, there was no essential oil constituent found in G. candida Gapnep. The main compounds of the rhizome extract of G. candida Gapnep were levoglucosan 19.07%, allylhydrazone acetaldehyde 5.52%, trans-2,3-epoxybutane 6.30%, butan-3-enoic acid methyl ester 4.36%, 2-methylcyclopentanone 4.02%, and 2-n-propyl-oxetan 4.00%. While the dominant contents of the leaves extract of G. candida Gapnep were pinostrobin chalcone 75.63%.